Antecedent of Father Involvement: A Literature Review - Ersa Lanang Sanjaya; Dewi Retno Suminar; Nur Ainy Fardana (Universitas Ahmad Dahlan, 2022)
Father involvement is an important aspect of the parenting process. Several studies have proven the positive influence of father involvement on children’s development. Unfortunately, both research on and implementation of parenting is still dominated by mothers, creating a need for studies on father involvement in child rearing. This literature review was compiled using three databases: Scopus, Sage and Science Direct. The main objective of this literature review is 1) to examine predictor variables of father involvement and 2) to assess the population of studies on father involvement. Forty-nine articles were analyzed in this review. The findings of this study show that research on paternal involvement in parenting is dominated by studies examining populations from a Western cultural context. In addition, most research on father involvement is rooted in the concept proposed by Lamb et al. (1985) in which paternal involvement is viewed through three dimensions: direct interaction, accessibility, and ultimate responsibility. Father-related, or individual, factors dominate the discourse of previous research as predictor variables of paternal involvement in parenting. A broader approach is required to determine predictor variables related to father involvement, due to the fact that there are many differences in the concept of family identity in non-Western cultures, especially in more communal societies. Research limitations are further explained in the article.